Local effect of IL‐4 delivery on polyethylene particle induced osteolysis in the murine calvarium1. Issue 7 (5th December 2012) - Rao, Allison J.; Nich, Christophe; Dhulipala, Lakshmi S.; Gibon, Emmanuel; Valladares, Roberto; Zwingenberger, Stefan; Smith, R. Lane; Goodman, Stuart B.
Abstract: Wear particles generated with use of total joint replacements incite a chronic macrophage‐mediated inflammatory reaction, which leads to implant failure. Macrophage activation may be polarized into two states, with an M1 proinflammatory state dominating an alternatively activated M2 anti‐inflammatory state. We hypothesized that IL‐4, an activator of M2 macrophages, could modulate polyethylene (PE) particle‐induced osteolysis in an experimental murine model. Four animal groups included (a) calvarial saline injection with harvest at 14 days (b) single calvarial injection of PE particles subcutaneously (SC) without IL‐4 (c) PE particles placed as in (b), then IL‐4 given SC for 14 consecutive days and (d) PE particles as in (b) then IL‐4 beginning 7 days after particle injection for 7 days. The calvarial bone volume to total tissue volume was measured using microCT and histomorphometry. Calvaria were cultured for 24 h to assess release of RANKL, OPG, TNF‐α, and IL‐1ra and isolation and identification of M1 and M2 specific proteins. MicroCT and histomorphometric analysis showed that bone loss was significantly decreased following IL‐4 administration to PE treated calvaria for both 7 and 14 days. Western blot analysis showed an increased M1/M2 ratio in the PE treated calvaria, which decreased with addition of IL‐4. Cytokine analysis showed that the RANKL/OPG ratio and TNF‐α/IL‐1ra ratio decreased in PE‐treated calvaria following IL‐4 addition for 14 days. IL‐4 delivery mitigated PE particle‐induced osteolysis through macrophage polarization. Modulation of macrophage polarization is a potential treatment strategy for wear particle induced periprosthetic osteolysis. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.